PEMILIHAN PRIORITAS KOMODITAS AGROWISATA MENGGUNAKAN METODE ANALYTICAL HIERARCHY PROCESS (AHP) DI DESA CANDIKUNING II, KEC. BATURITI, KAB. TABANAN. - Albina Br Purba, Susi; Hartiati, Amna; Tuningrat, Ida Ayu Mahatma (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 3 No 1 (2015): Maret, 2015)
The purposes of this research were to define priority of criteria to development of commodities for community based agro-tourism at village Candikuning II and to determine the type of commodity priorities. This research using Analytical Hierarchy Process (AHP) method, to define priorities and criteria agro commodities is a priority in the development of agro -tourism. Data obtained from interviews and questionnaires with five persons experts well experienced to development of commodities for community based agro -tourism. Results of interviews a nd questionnaires were analysed with AHP method use Excel program. The research concludes that the types of commodities that became the priority agro tourism at village Candikuning II based on the value of the priority are “strawberry”3.746,” ornamental plants / cutting flowers”2.101; and “vegetables” 1,209. The criteria that become priority criteria to development of commodities for community based agro -tourism village at Candikuning II are raw material (0.269); followed by technology used (0.184); marketing (0.169); employment (0.128); environmental aspects (0,113); investment (0.081); and than motivation of farmers (0.056).
Keywords: 34